"Normal" acute phase response in systemic sclerosis. Issue 6450 (13th October 1984) - Chellingsworth, M; Scott, D G; Crockson, P A; Bacon, P A
Abstract : An Italian woman with classic active progressive systemic sclerosis had a normal serum concentration of C reactive protein (less than 6 mg/1). During an infection with Staphylococcus aureus, however, the concentration rose to 250 mg/1. This was unexpected, since in scleroderma the acute phase response to infection (a brisk rise in serum concentrations of various proteins, including C reactive) has been thought to be defective. This patient is evidence that the acute phase response does occur in systemic sclerosis and that probably it is the nature of the primary disease that masks the response in some cases.